Nontraditional Monetary Policy Options : Is Commodity-Based Stabilization Policy Worth Another Look? - Richard C. K. Burdekin (Claremont McKenna College, Department of Economics, 2004)
The very low interest rates and inflation rates of recent years has generated renewed interest in alternative policies that would not leave central banks trapped by the zero lower bound on nominal interest rates. Amongst this debate, surprisingly little attention has been paid to the possibility of commodity purchases by the central bank, however. Commodity-based stabilization policy was widely advocated during the deflationary environment prior to World War II and has been put into practice in China and, to a more limited scale, in the United States in the form of the government's silver purchase programs and the more recent utilization of the Strategic Petroleum Reserve. This paper reviews these experiences and considers whether there is any useful scope for commodity-based stabilization today.
Keywords: N21; E42; 330; monetary policy; commodity standard; silver; open market operations; Geldpolitik; Konjunkturpolitik; Deflation; Öffentliche Beschaffung; Rohstoffmarkt; Offenmarktpolitik; Wirtschaftsgeschichte; Vereinigte Staaten; China